2017
DOI: 10.1186/s12944-017-0550-2
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of osteopontin, and osteoprotegerin mRNA in epicardial adipose tissue between patients with severe coronary artery disease and aortic valvular stenosis: association with HDL subclasses

Abstract: BackgroundPrevious studies suggest a relationship of the epicardial adipose tissue (EAT) with progression and calcification of the atherosclerotic plaque; however, it is unknown if this tissue expresses genes that may participate on these processes and if the expression of these genes is regulated by high-density lipoprotein (HDL) subclasses.MethodsTo explore this possibility, we determined the mRNA expression by qPCR of a pro-calcifying gene (osteopontin (OPN)), and two anti-calcifying genes (osteoprotegerin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 43 publications
1
15
0
1
Order By: Relevance
“…We have previously demonstrated that EAT expresses genes related with coronary calcification such as osteopontin (OPN), osteonectin (ON), and osteoprotegerin (OPG), 11 thus suggesting that EAT directly participates on coronary calcification. However, it remains unknown whether the pro-calcifying factors expressed by EAT are associated with the amount of calcium deposited in the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously demonstrated that EAT expresses genes related with coronary calcification such as osteopontin (OPN), osteonectin (ON), and osteoprotegerin (OPG), 11 thus suggesting that EAT directly participates on coronary calcification. However, it remains unknown whether the pro-calcifying factors expressed by EAT are associated with the amount of calcium deposited in the coronary arteries.…”
Section: Introductionmentioning
confidence: 99%
“…However, it remains unknown whether the pro-calcifying factors expressed by EAT are associated with the amount of calcium deposited in the coronary arteries. Since the coronary artery calcification (CAC) score was not determined in that exploratory study, 11 we recruited new groups of patients and controls in order to look for a potential biological impact of such mRNA expressions on coronary calcification. We quantified the CAC score and the EAT volume by tomography, as well as the gene expression in EAT from patients with coronary artery disease (CAD), including OPN, ON, OPG, and bone morphogenetic protein (BMP)-2 and BMP-4.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, osteopontin (OPN) it is a multi‐functional protein that promotes the inflammatory micro‐environment characteristic of the atherosclerosis. OPN increases with progression and calcification of the atherosclerotic plaque, suggesting a pro‐calcifying role of this protein .…”
mentioning
confidence: 99%
“…Indeed, ATMs are the primary source of pro-inflammatory mediators inside the adipose tissue and directly implicated in the pathogenesis of obesity-associated disorders, including cardiac and renal diseases [59][60][61][62]. In the last years, the CLs have become synonymous with metabolic dysfunction, perhaps for the rate of adipocyte death in obesity causing inflammation [58,63,64]. Intriguingly, it is demonstrated that OPN is expressed predominantly by ATMs in adipose tissue and regulates the local inflammation and cell death [60].…”
Section: Opn In Obesitymentioning
confidence: 99%
“…For this reason, it is highlighted that VAT is the main source of OPN during obesity [65]. In addition, the metabolic changes orchestrated by OPN in VAT [66,67] advance the hypothesis of its role as a key regulator of the inflammatory processes of obesity-induced adipose tissue inflammation [64] and become a possible target for treatment of adipose tissue-associated disorders, such as cardiac and renal diseases [15,17].…”
Section: Opn In Obesitymentioning
confidence: 99%